Pharmacotherapy: Its impact on morphofunctional characteristics of the epidermal barrier - D. D. Petrunin (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Various pharmaceuticals used for topical and systemic therapy are capable of exerting significant impact on morphological and physiological characteristics of human epidermis, as well as its barrier properties. This may affect the course of dermatologic diseases and the efficacy of their treatment. In this literature review, the author analyzes the impact of various pharmaceutical classes on the morphofunctional characteristics of the epidermal barrier and formulates recommendations for skin disease treatment.